Development of low‐shrinkage composites based on novel crosslinking vinylcyclopropanes. Issue 48 (25th August 2017) - Tauscher, Sven; Catel, Yohann; Fässler, Pascal; Fischer, Urs; Moszner, Norbert
ABSTRACT: Polymerization shrinkage of methacrylate‐based dental composites remains a major concern in restorative dentistry. Cyclic monomers that undergo ring‐opening polymerization are known to exhibit reduced polymerization shrinkage compared to methacrylates. In this article, the synthesis of four crosslinking 1, 1‐disubstituted 2‐vinylcyclopropanes bearing rigid spacers is described. These monomers were synthesized by esterification of 1‐ethoxycarbonyl‐2‐vinylcyclopropane‐1‐carboxylic acid with the corresponding diols. The photopolymerization kinetics of these monomers was investigated by photo‐differential scanning calorimeter using bis(4‐methoxybenzoyl)diethylgermane as the photoinitiator. The synthesized vinylcyclopropanes (VCPs) were shown to be more reactive than the frequently used reactive diluent triethylene glycol dimethacrylate. Composites based on these VCPs showed good mechanical properties and exhibited a significantly reduced volumetric shrinkage and shrinkage stress compared to a corresponding dimethacrylate‐based restorative material. This work highlights the excellent potential of VCPs as alternatives to methacrylates in the development of low‐shrinkage dental composites. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45577. Abstract :